2015
DOI: 10.1017/s026996481500008x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Markov-Modulated Infinite-Server Queues in the Central-Limit Regime

Abstract: This paper focuses on an infinite-server queue modulated by an independently evolving finite-state Markovian background process, with transition rate matrix Q ≡ (qij) d i,j=1 . Both arrival rates and service rates are depending on the state of the background process. The main contribution concerns the derivation of central limit theorems for the number of customers in the system at time t ≥ 0, in the asymptotic regime in which the arrival rates λi are scaled by a factor N , and the transition rates qij by a fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…We will see that the limit processes have intensities that are expectations under the invariant distribution of the chain. This is similar to what happens in the context of Markov modulated Ornstein-Uhlenbeck processes [18], see also [19], whereas comparable results under scaling in the operations research literature can be found in [5] and [6].…”
Section: Introductionsupporting
confidence: 86%
“…We will see that the limit processes have intensities that are expectations under the invariant distribution of the chain. This is similar to what happens in the context of Markov modulated Ornstein-Uhlenbeck processes [18], see also [19], whereas comparable results under scaling in the operations research literature can be found in [5] and [6].…”
Section: Introductionsupporting
confidence: 86%
“…When inflating the arrival rates by a factor N , and speeding up the background process by a factor N α (for some α > 0), in e.g. ( Anderson, Blom, Mandjes, Thorsdottir, and De Turck, 2014;Blom, De Turck, and Mandjes, 2015;Blom, De Turck, and Mandjes, 2016 ) it has been proven that the (transient as well as stationary) number of jobs present in the system is, after centering and normalizing, asymptotically Normally distributed. An interesting dichotomy was identified, in that the regimes α < 1 and α > 1 lead to qualitatively different asymptotics.…”
mentioning
confidence: 99%
“…3.3] that Z n α satisfies the LDP in M t with speed n α and rate function given by Eqn. (5). Since this rate function is finite everywhere (cf.…”
Section: The Markov-modulated Ornstein-uhlenbeck Processmentioning
confidence: 99%
“…We then consider the special case in which the background process is relatively slow, in which we find intuitively appealing results; notably, we prove that, along the most likely path, the background process jumps at most 2d − 2 times, with d the number of states of the background process; this is in stark contrast with earlier findings for the infiniteserver queue in [4], where the background process jumps at most d − 1 times. In previous work on modulated mean-reverting processes there was a strong focus on the central limit regime [2,5,13]; under various conditions convergence to an ordinary (i.e., non-modulated) OU process has been established. Related results on large deviations for modulated infinite-server queues can be found in e.g.…”
Section: Dm (T) = (α(J(t)) − γ(J(t))m (T)) Dt + σ(J(t)) Db(t)mentioning
confidence: 99%